The impact of nozzle temperature on the shrinkage of annealed 3D printed PLA - Sugianto, Sugianto; Meriatun, Meriatun; Pristiansyah, Pristiansyah; Ramli, Ramli; Wardiyah, Atikah Araminta; Hasdiansah, Hasdiansah; Herianto, Herianto (Politeknik Negeri Lhokseumawe, 2026)
Thermal annealing is used to strengthen the mechanical performance and thermal stability of fused deposition modeling (FDM) parts made from polylactic acid (PLA). This treatment frequently introduces dimensional shrinkage, compromising geometric accuracy and limiting the reliability of printed components in demanding applications. Among the printing parameters, nozzle temperature is a key variable because it influences melting behavior, interlayer diffusion, and the buildup of internal stresses, yet its role in managing shrinkage after annealing has not been clearly established. This study evaluates the influence of nozzle temperature on the anisotropic shrinkage of annealed PLA specimens across different specimen lengths and measurement directions (X and Y), with the main analysis conducted at selected nozzle temperatures ranged 195-230°C. Dimensional changes were quantified before and after annealing at 100°C for 60 min, and statistical evaluation was performed using analysis of variance (ANOVA) with post-hoc testing based on replicated specimens. The results confirm nozzle temperature as a significant contributor to shrinkage behavior, F (2,36) = 30.90, p 0.001, partial η²=0.63. Printing at 230°C consistently yielded the smallest dimensional reduction, outperforming both 210°C and 220°C. Within the examined range, 230°C emerges as the most effective nozzle setting for minimizing annealing-induced shrinkage, offering a practical processing window to improve dimensional accuracy and functional reliability in FDM-printed PLA parts.